Jarang Ganti Pembalut Meningkatkan Risiko Infeksi Gentalia Selama Menstruasi - Achmad, Arisandie Derezqi; Bambang, Purwanto; Wittiarika, Diah Ivon (Universitas Malahayati, 2024)
ABSTRACT In a survey conducted by WHO, the impact of poor Menstrual Hygiene Management (MHM) is often faced by women during menstruation. Maintaining hygiene during menstruation should not be taken lightly because if not done properly it will have a negative impact on women's reproduction. Germs and bacteria will grow and cause reproductive tract infections with skin irritation, unpleasant odor and genital infections. Frequency of changing pads is one of the symptoms of genital infection. To analyze the relationship between frequency of changing pads with symptoms of genatal infection during menstruation in female students of SMK DR. Soetomo Surabaya. This type of research is an observational analytic quantitative study using the cohort method in 10th and 11th grade students of SMK DR. Soetomo Surabaya. Each respondent was asked to fill out a questionnaire containing questions about menstruation and symptoms of genital infections. Data was analyzed statistically using contigency table and Chi Square test to prove between variables. The results of this study obtained a significant P-value of 0.024 which means that there is a significant relationship between the frequency of changing pads and symptoms of genital infections, after all female students experience menstruation for more than two weeks. After conducting the research, the researcher can conclude that the frequency of changing pads is a risk factor associated with genital infection. Keywords: Menstruation, Gentalia Infection, Adolescents ABSTRAK Dalam sebuah survei yang dilakukan oleh WHO dampak dari Manajemen Kebersihan Menstruasi (MKM) yang buruk kerap di hadapi perempuan saat menstruasi. Menjaga kebersihan saat menstruasi tidak boleh dianggap sepele sebab jika tidak dilakukan dengan benar akan memberikan dampak negatif bagi repsoduksi perempuan. Kuman dan bakteri akan tumbuh dan menimbulkan infeksi saluran reproduksi dengan iritasi pada kulit, bau tidak sedap hingga infeksi genetalia. Frekuensi ganti pembalut adalah salah satu gejala infeksi genetalia. untuk menganalisis hubungan antara freuensi ganti pembalut dengan gejala infeksi genatalia saat menstruasi pada siswi SMK DR. Soetomo Surabaya. jenis penelitian ini adalah penelitian kuantitatif analitik observasional dengan menggunakan metode kohort pada siswi SMK DR. Soetomo Surabaya kelas 10 dan 11. Setiap responden diminta mengisi kuesioner yang berisi pertanyaan tentang menstruasi dan gejala infeksi genetalia. Data di analisis secara statistiK menggunakan tabel kontigensi dan uji Chi Square untuk membuktikan antar variabel. Hasil dari penelitian ini diperoleh nilai signifikan P- Value sebesar 0,024 yang artinya terdapat hubungan yang bermakna antara frekuensi ganti pembalut dengan gejala infeksi genetalia, setelah semua siswi mengalami menstruasi lebih dari dua minggu. Setelah melakukan penelitian, maka peniliti dapat menyimpulkan bahwa frekuensi ganti pembalut merupakan faktor resiko yang berhubungan dengan gejala infeksi genetalia saat menstruasi. Kata Kunci: Menstruasi, Infeksi Gentalia, Remaja